Growth Performance on Sapudi Ewe’s Birth Typein Sapudi Island, Madura, East Java, Indonesia - Muarifah, H; Maharani, D; Bintara, S; Suparta Budisatria, I G (KnE Life Sciences, 2019)
This study aimed to compare the growth performance of Sapudi ewe based on birth type. A total of 60 ewes consisting of 35 single-birth type ewes and 25 prolific-birth type ewes were observed for data collection. The data for growth performance comprised of body length (BL), chest circumference (CC), wither height (WH) and udder circumference (UC). The results indicated that birth type significantly affected BL, CC, and WH (P < 0.05). The single-birth type showed greater BL, CC and WH values compared to prolific-birth type. However, no evidence suggested that UC (P = 0.262) are affected by birth type. The results can be useful for selecting Sapudi ewe based on the birth type and growth traits to improve the genetic performance in Sapudi Island, Indonesia. Keywords: birth type, BL, CC, growth performance, sapudi ewe, UC, WH